Spatiotemporal epidemiology of brucellosis in Iran from 2009 to 2018: A mixed ecological study - Sajjad Rahimi Pordanjani; Ghobad Moradi; Behrad Pourmohammadi; Elaheh Mazaheri; Farshid Farivar; Somayeh Derakhshan (Journal of Research in Medical Sciences)
Background: Brucellosis is one of the most common zoonotic diseases in the world. The present study was carried out to determine the epidemiological status of the brucellosis and identify the high-risk and low-risk clusters in different provinces of Iran. Materials and Methods: This was an ecological study conducted in the exploratory mixed design. The study population was the individuals with brucellosis in Iran whose data were related to the years 2009–2018. Data analysis has been done using Anselin Local Moran’s I, Global Moran’s I, Getis-Ord General G, Optimized Hot Spot Analysis, and Pearson correlation coefficient (PCC) in double range α and a significance level of 0.05. Results: The average annual incidence rate of the disease during the studied years was 19.91 per one hundred thousand. The three provinces with the highest cumulative prevalence rate included Lorestan, Hamedan, Kurdistan and the three provinces with the lowest prevalence rate involved Hormozgan, Tehran and Bushehr. Coldspots of brucellosis prevalence are in south and southwest of Iran and hotspots were observed in the west and northwest. The PCC between the prevalence rate and latitude was negative and not significant (r = −0.253; P = 0.169). However, a negative and significant correlation was found between the prevalence rate and longitude (r = −0.358; P < 0.05), indicating that as longitude increases, the prevalence of brucellosis decreases significantly. Conclusion: The prevalence of brucellosis in Iran is higher than developed countries and like many developing countries. High-risk areas of brucellosis were found in the western provinces and low-risk areas in the central and southern provinces of Iran. It appears essential to implement prevention and treatment measures in high-risk areas.